Efficacy of Reamed Intelocking Nail in the Management of Closed Tibal Shaft Fractures - Fatima, Fatima Rauf, Sobia Nawaz, Muhammad Adeem Busharat (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The purpose of this study is to evaluate the efficiency of reamed interlocking nails in the treatment of closed tibal shaft fractures. Study Design: The Observational and Descriptive study Place and Duration: Allied Hospital Faisalabad / Bahawal Victoria Hospital Bahawalpur.Jun 2018-Dec 2018. Material and Methods: A total of 130 patients, both sexes, were included in this analysis. Enrollees were between the ages of 18 and 60. After obtaining written agreement, the demographic information of registered patients was gathered and stored in a database. A reamed interlocking nail was used to repair tibial shaft fractures in patients brought to the emergency room. Postoperatively, the length of time it took to achieve union and the frequency of problems were also evaluated. During the course of 14 months, all of the patients’ follow-ups were completed. SPSS 24.0 was used to analyze the data. Results: Included patients had mean age 30.4±5.41 years and had mean BMI 23.13±8.51 kg/m2. Majority were males in this study. Most common cause of fracture was road traffic accident. In our study mean time of union among simple fractures were 11.53±14.61 weeks and mean union time of segmental fractures were 19.3±9.20 weeks. Among 130 cases, frequency of non-union fractures were 10 (7.7%), union fractures were 90 (69.2%) and delayed union were 30 (23.1%). Conclusion: A reamed interlocking nail was the most successful and safest treatment for closed tibal shaft fractures, according to this study. A total of 92.3% of the participants in this study were able to successfully consummate their unions.